1996
DOI: 10.1128/jvi.70.10.6673-6681.1996
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing human measles virus (MV) receptor CD46 provide cells exhibiting different permissivities to MV infections

Abstract: We have generated transgenic mice ubiquitously expressing the human receptor for measles virus (MV), CD46 (membrane cofactor protein). Various cell types were isolated from these transgenic mice and analyzed for their ability to support MV replication in vitro. Although MV could enter into all CD46-expressing cells, differential susceptibilities to MV infection were detected depending on the cell type. Cell cultures obtained from transgenic lungs and kidneys were found to be permissive of MV infection, since R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 44 publications
6
48
0
Order By: Relevance
“…A more detailed description of CD46 and SLAM expression in the normal and MV-infected CNS and peripheral tissues is currently in preparation (McQuaid et al, unpublished results). It has been shown that not all cells that are susceptible to MV infection express detectable levels of CD46 (Yanagi et al, 1994;Dunster et al, 1995;Horvat et al, 1996), and SLAM is only constitutively expressed on immature thymocytes, CD45RO high memory T cells, and a proportion of B cells (Sidorenko and Clarke, 1993;Cocks et al, 1995). The mechanism of MV entry into these cells remains unclear and would seem to indicate that other MV receptors may exist on mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed description of CD46 and SLAM expression in the normal and MV-infected CNS and peripheral tissues is currently in preparation (McQuaid et al, unpublished results). It has been shown that not all cells that are susceptible to MV infection express detectable levels of CD46 (Yanagi et al, 1994;Dunster et al, 1995;Horvat et al, 1996), and SLAM is only constitutively expressed on immature thymocytes, CD45RO high memory T cells, and a proportion of B cells (Sidorenko and Clarke, 1993;Cocks et al, 1995). The mechanism of MV entry into these cells remains unclear and would seem to indicate that other MV receptors may exist on mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Human herpesvirus 6 (HHV-6) and measles virus (MV) both use MCP as a cellular receptor, although they utilise different domains of this receptor for binding (Greenstone et al, 2002). Identification of MCP as the receptor for MV has led to the development of a transgenic mouse model that has contributed to in vivo studies of viral pathogenesis (Horvat et al, 1996;Rall et al, 1997). However, the primary MV receptor, signalling lymphocyte-activation molecule (SLAM) (Tatsuo et al, 2000), is not part of the complement system.…”
Section: Direct Binding To Complement Receptors and Regulatorsmentioning
confidence: 99%
“…Human parainfluenza virus 1, 3 Sialic acid residues on gangliosides glycolipids (Suzuki et al, 2001) Measles virus CD46 (Dorig et al, 1993;Naniche et al, 1993;Schneider-Schaulies et al, 1995;Horvat et al, 1996;Buckland and Wild, 1997;Buchholz et al, 1997;Niewiesk et al, 1997); SLAM (Tatsuo et al, 2000b)…”
Section: Ebola Virusmentioning
confidence: 99%